The Effect of Problem Based Learning (PBL) Model Based on Local Wisdom to Improve Students' Critical Thinking Skills - Cahayu, Sri Anika; Siburian, Jodion; Hamidah, Afreni (Integrated Science Education Journal, 2024)
Purpose of the study: The purpose of this study was to determine the effect of problem-based learning (PBL) model based on local wisdom in making lemang kancung beruk to improve students' critical thinking skills. Methodology: The research method is a quasi-experimental form of non-equivalent pretest-posttest control group design with non-probability sampling technique-purposive sampling. The data collection techniques used critical thinking skills tests with FRISCO indicator essay tests and observation sheets. Technical data analysis used Analysis of covariance (Ancova) test and quantitative descriptive approach used SPSS 20 program. Main Findings: The research results of the Ancova hypothesis test show that the corrected model sig value is 0.000 <0.05, then H0 is rejected and H1 is accepted, This means that the problem-based learning (PBL) model based on local wisdom in making lemang kancung beruk has a significant and moderate effect on improving students' critical thinking skills. Novelty/Originality of this study: The novelty of this research is the implementation of problem-based learning (PBL) model based on local wisdom of Kerinci-Sungai Penuh area in science learning. The limitations in the study are the competencies measured in the integrated essay test and the subject matter is the science material of substances and their changes in class VII.